2018
DOI: 10.15244/pjoes/78044
|View full text |Cite
|
Sign up to set email alerts
|

Lotic Ecosystem Health Assessments Using an Integrated Analytical Approach of Physical Habitat, Chemical Water Quality, and Fish Multi-Metric Health Metrics

Abstract: This study evaluates integrative lotic ecosystem health using neural network modeling and principal component analysis of physical, chemical, and biological parameters in 33 streams and rivers of a large watershed. Water chemistry parameters were measured to detect chemical health, and physical habitat health was determined by a model of qualitative habitat evaluation index (QHEI). Also, biological health was determined by the multi-metric community fish model of index of biological integrity (IBI) and then an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
3
10
0
1
Order By: Relevance
“…CHL, TSS, TNI, AI, N:P were the most important factors for the prediction of IBI value in the watershed. Our present study suggested that the statistical learning approach ANN is one of the good tools to predict the ecological health of the river system, which is concurred with the previous studies of Lee et al 2018 [28].…”
Section: Prediction Of Chemical Pollution Index and Index Of Biotic Isupporting
confidence: 92%
See 3 more Smart Citations
“…CHL, TSS, TNI, AI, N:P were the most important factors for the prediction of IBI value in the watershed. Our present study suggested that the statistical learning approach ANN is one of the good tools to predict the ecological health of the river system, which is concurred with the previous studies of Lee et al 2018 [28].…”
Section: Prediction Of Chemical Pollution Index and Index Of Biotic Isupporting
confidence: 92%
“…A total of 44 species were observed in the mainstream of the Geum River watershed. The dominated species in the watershed were Zacco platypus (32.99%), Zacco koreanus (12.43%), and Squalidus chankaensis tsuchigae (11.19%), etc., which was similar with some previous studies on watershed [28]. One endangered species (Pseudopungtungia nigra) was found in the upstream of the watershed.…”
Section: Fish Community Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…The water quality in these ecosystems is determined by various interactions of natural and anthropogenic factors [Lake et al 2017]. The increase in industrial, fishing, agricultural and recreational activities generate changes in water quality due to cumulative effects, causing great economic and ecological losses [Lee et al 2018].…”
Section: Introductionmentioning
confidence: 99%